From Thinking to Doing: Effects of Different Social Norms on Ethical Behavior in Journalism. Issue 2 (2nd April 2016) - Lee, Angela M.; Coleman, Renita; Molyneux, Logan
ABSTRACT: Journalists have been shown to be highly capable of making good moral decisions, but they do not always act as ethically as studies show them to be able. Using the Reasoned Action Model, this study explores the gap between moral motivation and moral behavior and tests the proposition that different social norms can help predict how journalists behave across three ethical and three unethical behaviors ( N =374). The study found that descriptive norms predicted ethical behaviors and that injunctive norms predicted unethical behaviors. Descriptive norms also accounted for more variance in journalists' ethical behavior (48%) than injunctive norms did on unethical behavior (28%). The findings advance the Four-Component Model in significantly improving moral behavior predictability and offer a new way to assess journalists' moral reasoning.